Workplace accommodation to people with disabilities: a case study in civil construction - Bruno Guimarães; Laura Bezerra Martins; Béda Barkokébas Junior
Abstract Objective : the aim of this paper was to assess and describe the various tasks of the jobs of servant of construction, bricklayer, painter and charge of construction in the civil construction to determine the profile of workers with disabilities who could perform these functions and what adjustments are needed. Methods : this research it is a descriptive cross-sectional quantitative approach. Direct observation of the activities performed at the construction site in each of the jobs evaluated and the environment; interviews with two workers each function evaluated, except painter there was only one worker, a civil engineer and a safety technician to describe detailed, together, as they were carried out each of the required tasks; a video and photographic record of tasks being carried out to analyze the jobs, ErgoDis/IBV software resources were used. At the time the research was conducted in the field, were working a total of 1,547 employees. Results : It was observed that workers with hearing impairments could perform the activities without any adaptations in the workplace and individuals who had had a leg or foot amputated need to use appropriate prostheses to perform the activities of the functions. Conclusion : only workers with full or partial hearing impairment could perform all the jobs analyzed without any accommodation in the workplace and individuals with amputation of leg or foot may only perform tasks using appropriate aids.